2003
DOI: 10.4049/jimmunol.171.1.61
|View full text |Cite
|
Sign up to set email alerts
|

Homeostasis of Naive and Memory CD4+ T Cells: IL-2 and IL-7 Differentially Regulate the Balance Between Proliferation and Fas-Mediated Apoptosis

Abstract: Cytokines play a crucial role in the maintenance of polyclonal naive and memory T cell populations. It has previously been shown that ex vivo, the IL-7 cytokine induces the proliferation of naive recent thymic emigrants (RTE) isolated from umbilical cord blood but not mature adult-derived naive and memory human CD4+ T cells. We find that the combination of IL-2 and IL-7 strongly promotes the proliferation of RTE, whereas adult CD4+ T cells remain relatively unresponsive. Immunological activity is controlled by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
75
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 88 publications
(77 citation statements)
references
References 65 publications
2
75
0
Order By: Relevance
“…More recently it has been established that a disruption of T cell homeostasis through the persistent stimulation of naïve cells, pushing them along the path of differentiation, is a contributing factor to HIV disease progression [2, 8,9]. Under normal conditions, when there is a reduction of T cell numbers in the periphery, levels of IL-7 increase to send survival signals via the IL-7R to promote antigen independent, or homeostatic proliferation to rebalance T cell numbers [16,44]. In lymphopenic HIV-infected individuals, there is an elevated level of IL-7 caused by the homeostatic response to T cell depletion [45,46].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…More recently it has been established that a disruption of T cell homeostasis through the persistent stimulation of naïve cells, pushing them along the path of differentiation, is a contributing factor to HIV disease progression [2, 8,9]. Under normal conditions, when there is a reduction of T cell numbers in the periphery, levels of IL-7 increase to send survival signals via the IL-7R to promote antigen independent, or homeostatic proliferation to rebalance T cell numbers [16,44]. In lymphopenic HIV-infected individuals, there is an elevated level of IL-7 caused by the homeostatic response to T cell depletion [45,46].…”
Section: Discussionmentioning
confidence: 99%
“…Although many correlates have been identified that may influence the rate of HIV progression, including immune activation, and the disruption of T cell homeostasis, a complete understanding of the mechanisms of CD4 + T cell decline remains elusive [1][2][3][4][5][6][7][8][9][10][11][12][13][14]. Cytokines that signal through the common gamma chain, such as IL-2, IL-4, IL-7, and IL-15, are some of the main mediators of T cell homeostasis [15][16][17][18][19][20][21]. This study focused on one of these cytokine receptors, the IL-7R.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…IL-2 controls T-cell clonal expansion and contraction, and promotes lymphocyte differentiation. IL-2 and IL-15 can also support memory cell division and have been used in combination with Ag-driven stimulation, for the expansion of CTL [24][25][26][27][28][29]. IL-7 regulates peripheral T-cell homeostasis, and contributes to the generation and long-term survival of both CD4 1 and CD8 1 memory T lymphocytes in vivo [30,31].…”
mentioning
confidence: 99%
“…The increased concentration of IL-7 found in T cell-depleted individuals is considered to be a homeostatic response to T cell depletion, which may accelerate thymic output and promote peripheral T cell survival and proliferation (22,29,30). In addition to the extensive data on T cell maintenance by IL-7, it has also been suggested that IL-7 might participate in the up-regulation of Fas expression on naive T lymphocytes (34,35). Another study described IL-7 as a stimulator of Fas-induced apoptosis in T cell cultures infected with HIV-1 (36).…”
mentioning
confidence: 99%